2020
DOI: 10.12659/msm.920039
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Erythropoietin on Lung Injury Induced by Cardiopulmonary Bypass After Cardiac Surgery

Abstract: Background:Lung injury after cardiopulmonary bypass (CPB) is a serious postoperative complication and can affect the postoperative recovery. The purpose of this study was to explore whether erythropoietin (EPO) has an effect on lung injury caused by CPB. Material/Methods:Sixty patients who received the CPB were randomly divided into a saline group and the EPO group. All the patients received saline or EPO preoperatively, respectively. The ventilation function, including dynamic compliance, peak airway pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 33 publications
(36 reference statements)
0
7
0
Order By: Relevance
“…CPB lung injury is one of the main complications after cardiovascular surgery, and it is also an important cause of postoperative patient death [18] . Studies have shown that tumor necrosis factor and interleukin produced after CPB can directly damage endothelial cells, increase capillary permeability, cause pulmonary edema, and can also promote neutrophils, and macrophage In ltration and release of cytotoxic enzymes aggravate lung injury [19] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CPB lung injury is one of the main complications after cardiovascular surgery, and it is also an important cause of postoperative patient death [18] . Studies have shown that tumor necrosis factor and interleukin produced after CPB can directly damage endothelial cells, increase capillary permeability, cause pulmonary edema, and can also promote neutrophils, and macrophage In ltration and release of cytotoxic enzymes aggravate lung injury [19] .…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the S group, the expression of AnxA1 in the lung tissues of the I/R, D, A, and AL groups Discussion CPB-induced lung injury, one of the main complications after cardiovascular surgery, a dominant factor of postoperative death. 16 Studies have revealed that tumor necrosis and interleukin produced after CPB directly damage endothelial cells, increase capillary permeability, cause pulmonary edema, and promote infiltration of neutrophils and macrophage. The resulting release of cytotoxic enzymes aggravates lung injury.…”
Section: Levels Of Tumor Necrosis Factor-alpha In Lung Tissues and Th...mentioning
confidence: 99%
“…During pulmonary ischemiareperfusion, in ammatory cells in ltrate, pulmonary interstitial exudation increases, and microvilli on the surface of type II alveolar epithelial cells decrease in abundance. Therefore, patients are more likely to have complications such as alveolar collapse, atelectasis, acute respiratory failure, pulmonary infection, and so on [14,15]. At the same time, during invasive mechanical ventilation, alveolar mechanical ectasia and partial alveolar structure destruction cause lung injury and airway remodeling [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…EPO was found to decrease pro-inflammatory cytokine production, including intercellular adhesion molecule-1 (ICAM-1) [46], interleukin-6 (IL-6) [47], and TNF-α [48,49]. EPO also increased the production of the anti-inflammatory cytokine IL-10 [48]. Additionally, EPO could increase endothelial nitric oxide synthase (eNOS) protein expression (Figure 1) [50], which increase nitric oxide production.…”
Section: Anti-inflammatory Effectsmentioning
confidence: 99%
“…Hence, the potential anti-inflammatory effect of EPO has also been investigated. EPO was found to decrease pro-inflammatory cytokine production, including intercellular adhesion molecule-1 (ICAM-1) [46], interleukin-6 (IL-6) [47], and TNF-α [48,49]. EPO also increased the production of the anti-inflammatory cytokine IL-10 [48].…”
Section: Anti-inflammatory Effectsmentioning
confidence: 99%